La Charte marocaine de l’Environnement et du Développement durable sera-t-elle une loi fondamentale ? - Samira Idllalène (VertigO)
By his majesty's request, the king of Morocco has led an effort in introducing the bill of the national charter of environment and sustainable development (CNEDD). This bill was put together by an interdepartmental commission and intends to be a turning point in the country's environmental policy. The end result and summary of the text may lead you into wondering about its real value while the royal speech that initiated it seems to indorse the idea of adding it to the Constitution. However, the last throne speech (july 2010) gives the impression of giving up on this idea. Will CNEDD be a fundamental law, a framework law or a simple declaratory text with inciting value? This article means to record its true "added value" by mainly checking the feasibility of its constutional form.